DDOS Mitigation In Cloud Computing Environment By Dynamic Resource Scaling With Elastic Load Balancing - et. al., A. Somasundaram, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The major attack in cloud computing is Distributed Denial of Service (DDoS) which brings more attention to cloud users in the past decade. A DDoS attack can be avoided or controlled by allocating enough resources whenever demanded. Resource allocation will induce additional costs when the attacks reside for a long duration or more frequently. To control and avoid the DDoS attacks dynamic resource allocation has been employed in specific target services for mitigating the attack effectively. During the attack, the resources are overloaded with higher usage and lead to denial of required service for legitimate users forcefully. By adjusting the resource utilization, the attacks can be completely mitigated by which the genuine users' request for the resources can be apparently handledbesidesthe disbandment of established connection with the attacker’s node. Thus resource utilization factor plays a significant role in attack mitigation and recovery which is the number of various resources allocated to the victim service. In this research, a new method has been proposed to evaluate the resource utilization by ‘scaling down the resources’which is an enhancement of the 'scale inside out' model. The proposed method exploits the usage of two components such as verification module and elastic load balancer in order to detect and mitigate the DDoS attack commendably.This enhanced method optimally reduces the resource utilization factor through elastic load balancing by analyzing the incoming traffic data and server condition. The main idea of scaling down the resources and services is to sacrifice the victim’s resources during an attack period in order to mitigate the effect and recover from the attack. The performance of the proposed model is evaluated using various metrics to analyze the attack detection time, attack reporting time, and attack mitigation time. The results show that the proposed method works well to mitigate the DDoS attack by consuming the minimum resources thereby decreasing the service time of the user